Ingestion of ‘whole cell’ or ‘split cell’ Chlorella sp., Arthrospira sp., and milk protein show divergent postprandial plasma amino acid responses with similar postprandial blood glucose control in humans - Williamson, Ellen; Monteyne, Alistair J.; Van der Heijden, Ino; Abdelrahman, Doaa R.; Murton, Andrew J.; Hankamer, Benjamin; Stephens, Francis B.; Wall, Benjamin T. (Frontiers in Nutrition, 2024)
Microalgae provide a sustainable basis for protein-rich food production. However, human data concerning microalgae ingestion, subsequent postprandial amino acid (AA) availability and associated metabolic responses are minimal. We investigated ingesting Arthrospira sp. (spirulina;SPR), and Chlorella sp. (chlorella; in 'whole cell' [WCC] and 'split cell' [SCC] forms, the latter proposed to improve digestibility), compared with with a high-quality animal derived protein source (milk; MLK). Ten participants (age; 21±1y, BMI; 25±1kg•m -2 ) completed a randomised, crossover, double-blind study, partaking in 4 counterbalanced (for order) experimental visits. At each visit participants ingested SPR, WCC, SCC or MLK drinks containing 20g protein and 75g carbohydrate. Arterialised venous blood samples, indirect calorimetry and visual analogue scales were assessed postabsorptive, and throughout a 5h postprandial period to measure AA, glucose, insulin and uric acid concentrations, whole-body energy expenditure and appetite scores, respectively. Protein ingestion increased plasma AA concentrations (P<0.001) to differing total postprandial total-and essential-AA availabilities; highest for MLK (86.6±17.8mmol.L -1 ) and SPR (84.9±12.5mmol•L -1 ), lowest for WCC (-4.1±21.7mmol•L -1 ; P<0.05), with SCC (55.7±11.2mmol•L - 1 ) marginally greater than WCC (P=0.09). No differences (P>0.05) were detected between conditions for postprandial glucose or insulin concentrations, whole-body energy expenditure or appetite scores, but serum uric acid concentrations increased (P<0.05) following microalgae ingestion only. Our data imply that microalgae can present a bioavailable source of protein for human nutrition, however, challenges remain, requiring species selection and/or biomass processing to overcome.